SILAGEM DE RAÇÃO COMPLETA À BASE DE PALMA FORRAGEIRA E LEGUMINOSAS: CARACTERÍSTICAS FERMENTATIVAS, POPULAÇÕES MICROBIANAS, ESTABILIDADE AERÓBIA E VALOR NUTRITIVO - LOPES, Rosilda da Conceição (2020)
The objective of this experiment was to evaluate the fermentative profile, fermentative losses, microbial populations, aerobic stability, chemical composition and in situ degradability of complete feed silages based on forage palm associated with legumes. The treatments consisted four complete feed silages based on the forage palm and concentrate SRPC and associated wiht legumes such as gliricidia SRPG, leucena SRPL and pasture-kills SRPMP. There was a difference (P< 0.05) between the treatments evaluated, for the pH and N-NH3 variables, the pH values evaluated within the ideal range 4.2 a 4.4, as N-NH3 paramerers varied from 2.21 to 0.85%. The dry matter recoveries for the treatments evaluated were on average 89%. The populations of lactic acid bacteria (BAL) ranged from 5 to 6.3 log CFU/ g MF among the evaluated silages. All feed silages associated with legumes dissipated for molds averaged 3.3 log CFU/g MF. Yeast populations were observed only for one SRPG 5 log CFU/g MF. As greater aerobic stability was observed for na SRPC, the SRPG followed by the SRPMP. The chemical composition of the complete feed silages was as expected by the combination of the diets. The SRPC stands out in relation to the other feed silages, for presenting the highest soluble fration (A) and the highest effective degradation (DE) for the three passage rates evaluated (2%/h; 5%/h and 8 %/h). It is concluded that the feed silages associated with leguminous gliricidia and pasture-kills can be recommended, based on fermentation and nutritional value.